Efektivitas Implementasi Kebijakan Rencana Pemindahan Lokasi Industri - Industri di Kawasan Simongan ke Kawasan Industri Pada Rencana Tata Ruang Kota Semarang - Ratna Sari, Diah Ayu (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
Semarang Spatial Planning 2011 - 2031 has been prepared and approved in Semarang City Regulation No. 14 /2011. The development of industrial activities in the city of Semarang is more limited as it refers to the vision of Semarang promote the development of trade and services sector. Industries in the region Simongan not been allocated in the Spatial planning when there are Â± 12 companies with an area of about 50 acres with thousands of employees. These industries have existed since the 1950s. Industries that occupy locations outside the industrial zone is seen as a violation of the regulations. As a form of space utilization control of Semarang Spatial Planning, the industrial activities are still outside of the industry will be relocated gradually and if not implemented, sanctions should be given. Communities and employers reject the policy. The role of industry to the economy of the surrounding area is quite significant. Research related to the effectiveness of government policy implementation is considered very necessary to know how the effectiveness of policy implementation as space utilization control enforcement efforts on industries in the region Simongan? Policy is not implemented properly so that no effective implementation. Stages of research studies the effectiveness of policy implementation through discussions studies of industrial location policy resettlement plan; study of perceptions of government, industry and society.